Efeito da farinha da batata yacon (Smallanthus Sonchifolius) sobre o perfil glicêmico de ratos - ROSA, Lorena Pereira de Souza (2011)
The morbidity and mortality profile of the Brazilian population has changed recently in light of the increasing prevalence of chronic noncommunicable diseases. Of particular importance among these diseases is diabetes, a multiple-etiology disease characterized by insulin deficiency or decreased insulin production, or both. A major treatment goal is glycemic control, which requires medications that are expensive and have side effects. As a result, the demand for functional foods to complement this treatment is increasing. Among these foods is the yacon potato. To confirm its antidiabetic activity, glycemic profile studies in animals and humans have been carried out. The aim of this study was to evaluate the effect of yacon potato (Smallanthus sonchifolius) flour on glycemic control in nondiabetic rats and rats with streptozotocin-induced diabetes. Flour was prepared from vacon potato pulp and later a biological assay was carried out. Yacon potato flour was able to lower mean glycemia in diabetic rats, which can be explained by the FOS reserve. Animals treated with a FOS diet also had reduced blood glucose levels, confirming the ability of these fructans to control glycemia. The diabetes mellitus induction methodology proved effective, which validated the induction protocol developed. These results suggest that long-term studies with the diabetes model can best be assessed in relation to glycemic control, since there was better control starting in the third week of experiment.